Transferência de tecnologia e gestão da propriedade intelectual em universidades públicas no Estado de São Paulo - Garnica, Leonardo Augusto (Universidade Federal de São Carlos, 2007)
The importance of the technology management in Brazilian public universities has been increasing due to the great potential regarding technology transfer from those organizations to industries. After the Innovation Law in 2004, this point of view has been encouraged by the establishment of specific guidelines regarding intellectual property, technology cooperation with outside organizations and the role of universities in scientific and technological development, as a part of the Brazilian innovation system. In this context, the objective of this work was to understand how the public universities of the State of São Paulo structure their regulation of intellectual property and technology transfer processes for companies, as well as to identify forces and obstacles for that practice. The empiric part of the work consisted of five case studies in public universities located in the State of São Paulo, using exploratory and qualitative analysis. The universities studied were: University of São Paulo (USP), São Paulo State University - Unesp, State University of Campinas (Unicamp), Federal University of São Paulo (Unifesp) and Federal University of São Carlos (UFSCar). All the regulations of intellectual property that affect the technological management in those universities were researched, as well as information concerning patenting performance and technology commercialization, including interviews with university technology managers. In order to gain full understanding of how the technology transfer process happens, illustrative studies were carried out, using a contract from each one university (patent licensing or sponsor research contract) involving companies. The results of the work were divided in two categories. A first comparison of more restricted character involved illustrative studies of technology transfer of processes from the five universities. The second, a more in-depth approach, involved considerations concerning technology management in these universities. Regarding the first perspective, the results were shown as a schematic representation for each process, with similar indicatives in juridical-administrative terms. We also analyzed the relationship between the people involved in technology transfer and the characteristics of the organizations involved in it. As a general conclusion, it was noticed that formal technology transfer using intellectual property has been growing in the public universities of the São Paulo State. We could also observe that a process of physical and personnel structuring is taking place in all the cases and that all the universities concerned have intellectual property regulations. The comparative analysis carried out shows which universities are more actively involved in patenting and technology commercialization. The results also demonstrate and discuss the challenges that have been identified for the improvement of technology transfer in these universities. The main ones are: the spread of the intellectual property culture, technology evaluation, establishment and consolidation of best practices in management and international technology protection, as well as alignment of policies among the institutions which share and generate intellectual property.
Keywords: Transferência de tecnologia; Propriedade intelectual; Cooperação universidade e empresa; Gestão da inovação; Technology Transfer; Intellectual Property; University-Industry Cooperation; ENGENHARIAS::ENGENHARIA DE PRODUCAO